2012
DOI: 10.1097/mph.0b013e31821ba989
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastic Fibrosarcoma of the Mandible

Abstract: Ameloblastic fibrosarcoma (AFS) is a rare malignant odontogenic tumor. We report 2 pediatric cases of AFS from 2 different centers but reviewed by the same pathologist, which were unusual in that they were chemosensitive. Management was wide surgical resection, chemotherapy, and adjuvant radiotherapy. One case was a local AFS recurrence after incomplete surgery and the other was an AFS that was overlooked during earlier diagnosis of an ameloblastic fibroma. Both tumors responded very well to preoperative chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…According to cases reported, no significant difference was observed in age and sex distribution between our case and those in the literature [ 12 ]. Although either the maxilla or the mandible may be involved, AFS more frequently occurs in the mandible (79%) than the maxilla (21%) and most that were similar to our case were found in the posterior region of the mandible [ 10 ]. Clinical appearance and symptoms vary among the reported cases, but swelling and pain are the most common clinical findings, as in our patient.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…According to cases reported, no significant difference was observed in age and sex distribution between our case and those in the literature [ 12 ]. Although either the maxilla or the mandible may be involved, AFS more frequently occurs in the mandible (79%) than the maxilla (21%) and most that were similar to our case were found in the posterior region of the mandible [ 10 ]. Clinical appearance and symptoms vary among the reported cases, but swelling and pain are the most common clinical findings, as in our patient.…”
Section: Discussionsupporting
confidence: 69%
“…Ameloblastic fibrosarcoma is usually regarded as a low-to-intermediate-grade malignancy. It has locally aggressive behavior and a high recurrence rate, but rarely metastasizes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant radiotherapy has been used with no evidence of recurrence [ 9 ]. Adjuvant chemotherapy has also been used with moderate success [ 17 ], although no specific chemotherapy protocols have been established yet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported varying demography for AFS, probably because most were small series or case reports. Martinez et al [ 7 ] reported a mean age of 19 years while others reported a mean age of 27.3 years and AFS is reported to be the most common MOT in paediatric age group [ 7 , 22 ].…”
Section: Discussionmentioning
confidence: 99%